Why don't more patients receive intravenous rt-PA for acute stroke?. (June 2015) - Lyden, Patrick
<x xml:space="preserve">Abstract</x> Intravenous rt-PA was proven safe and effective for acute ischemic stroke in 1995, approved by US FDA in 1996, and endorsed by the American Heart Association, American Academy of Neurology, and National Stroke Association in 1997. The treatment is remarkably cost-effective, despite the high cost of the drug itself and the stroke teams to give it. Community-based practicing neurologists can use t-PA for acute stroke without the need for specialized expertise. The benefit is durable over long-term follow-up and no particular subgroups, such as the elderly or those with very large strokes, should be excluded from treatment. Several additional studies have now confirmed the beneficial effects of thrombolytic therapy for stroke in de novo samples. So why isn't the drug used more? Some troubling mis-understandings in the literature seem persistent and influential among clinicians. Considerable data supports the use of rt-PA for acute ischemic stroke, which should remove remaining doubts.